PENGARUH FAKTOR DEMOGRAFIS DAN PSIKOLOGIS PADA KINERJA ACCOUNT REPRESENTATIVE DIREKTORAT JENDERAL PAJAK - Yunita, Eva; Wirama, Dewa Gede; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
This study analyze s whether demographic and psychological factors a ffect the performance of account representatives of the Directorate General of Taxes. Demographic factors in this study represented by age, gender, and the length of work experience. Psychological factors represented by personality-job fit and psychological capital. Total sampel are 384 account representative s who were willing to fill out the research questionnaires distributed online. The data were analyzed using multiple linear regressions. The analysis show s that age, the length of work experience, personality-job fit, and the psychological capital have a positive e ffect on the performance of the account representatives , while t he gender does not a ffect the performance of account represent ati ive s . The results of this study could be used by the Directorate General of Taxes as a reference in the placement and development of its account representative s.
Keywords: performance, theory of personality, personality-job fit, psychological capital, age, gender, the length of work experience